2012
DOI: 10.5402/2012/306816
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in Scaling of Gait Force and Cycle in Parkinsonian Gait Identified by Long-Term Monitoring of Acceleration with the Portable Gait Rhythmogram

Abstract: To examine the range of gait acceleration and cycle in daily walking of patients with Parkinson's disease (PD), we compared the gait of 40 patients with PD and 17 normal controls by using a newly developed long-term monitoring device that extracts gait-related accelerations from overall movements-related accelerations. The range of change in gait acceleration, relative to the control, was less than 75% in 12 patients. The range of change in gait cycle was less than 75% in 8 patients. The range of changes in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Previously, we reported that SARA did not correlate with the total length traveled or the root mean square area of body sway as measured 11 by body stabilometry [8]. Some reports of gait analysis in PD patients have evaluated acceleration, but not amplitude or CV [9].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Previously, we reported that SARA did not correlate with the total length traveled or the root mean square area of body sway as measured 11 by body stabilometry [8]. Some reports of gait analysis in PD patients have evaluated acceleration, but not amplitude or CV [9].…”
Section: Discussionmentioning
confidence: 77%
“…Previously, we reported that SARA did not correlate with the total length traveled or the root mean square area of body sway as measured 11 by body stabilometry [8]. Some reports of gait analysis in PD patients have evaluated acceleration, but not amplitude or CV [9].Menz et al reported that the magnitude of pelvis accelerations increased, while head accelerations were not affected by the walking surface when walking on an irregular surface [10]. In the present study, when we compared each parameter of the healthy control group by upper and lower back, the CV of ML and VT were lower in the upper back, while the CV of AP was lower in the lower back.…”
mentioning
confidence: 78%
“…The PGR is a trunk-mounted small device (size, 8×6×2 cm, weight, 80 g) ( Figure 1) housing an acceleration sensor with automatic gait detection algorithm, in which gait induced-accelerations are extracted from limb and trunk movements using a mathematical algorithm; the "pattern matching method" [13][14][15][16][17][18][19][20]. …”
Section: Methods: Gait Rhythmography For Monitoring Gaitinduced Accelmentioning
confidence: 99%
“…Continuous recordings of walking movements during daily activities also clarified how gait parameters are voluntarily controlled. We proposed the technique of gait acceleration-cycle plot, to examine how the gait is voluntarily controlled [15,17,18].…”
Section: Subjective Motor Fluctuation In Pd Does Not Necessarily Corrmentioning
confidence: 99%
See 1 more Smart Citation